Influência de diferentes tipos de recuperação sobre a modulação autonômica cardíaca, concentração de lactato e proteína C-reativa - Bastos, Fábio do Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
A recuperação pós-exercício consiste em restaurar os sistemas do corpo à sua condição basal, proporcionando equilíbrio e prevenindo a instalação de lesões e, nesse sentido, torna-se aspecto importante de todo programa de condicionamento físico, em quaisquer níveis de desempenho, mas, sobretudo nos mais elevados. O objetivo desta revisão foi reunir informações e descrever as respostas proporcionadas por métodos recuperativos pós-exercício como, crioterapia, contraste, massagem e recuperação ativa, constituindo uma fonte de atualização do referido tema. Utilizou-se os bancos de dados, MedLine, Scielo e Lilacs, como lista de periódicos o SportsDiscus. Foram incluídos no estudo somente ensaios clínicos randomizados controlados e não-controlados além de artigos...

The post-exercise recovery consists in restoring the body systems to baseline condition, providing balance and preventing injuries installation and, in that sense; it becomes an important aspect of every fitness program, at any levels of performance, but especially in higher levels. The objective of this review was to gather information and to describe the responses provided by post-exercise recovery methods, such as cryotherapy, contrast water immersion, massage and active recovery, providing an update on this issue. MedLine, Scielo and Lilacs databases were used, as well as the SportsDiscus list of journals. Only randomized controlled and non-controlled clinical essays, in addition to review articles concerning the proposed topic were included. Our choice was for the search terms: cryotherapy, massage, active recovery, thermotherapy, immersion and exercise, individually and combined. It was observed that some studies report that cryotherapy is harmful concerning post-exercise recovery, once it reduces performance immediately after the technique... (Complete abstract click electronic access below)
Keywords: Fisioterapia; Marcadores biologicos; Cryotherapy; Massage; Recovery of function; Immersion